A Census-Level, Multi-Grade Analysis of the Association Between Testing Time, Breaks, and Achievement. Issue 1 (2nd January 2023) - Rutkowski, David; Rutkowski, Leslie; Valdivia, Dubravka Svetina; Canbolat, Yusuf; Underhill, Stephanie
ABSTRACT: Several states in the US have removed time limits on their state assessments. In Indiana, where this study takes place, the state assessment is both untimed during the testing window and allows unlimited breaks during the testing session. Using grade 3 and 8 math and English state assessment data, in this paper we focus on time used for testing and examine whether students who take more time tend to outperform their peers. Further, we also examine if the number of breaks students take is associated with student achievement scores. Findings suggest that even in an untimed setting, there remains a strong association between time spent on the assessment and achievement at both the student and school level. The number of breaks, on the other hand, show little to no association with achievement after controlling for time. The paper concludes with a discussion of the policy implications of the findings.